Dual regulation of lin28a by Myc is necessary during zebrafish retina regeneration - Mitra, Simran; Sharma, Poonam; Kaur, Simran; Khursheed, M.A.; Gupta, Shivangi; Chaudhary, M.; Kurup, A.J.; Ramachandran, Rajesh (Rockefeller University Press, 2019)
Cellular reprogramming leading to induction of Muller glia–derived progenitor cells (MGPCs) with stem cell characteristics is essential for zebrafish retina regeneration. Although several regeneration-specific genes are characterized, the significance of MGPC-associated Mycb induction remains unknown. Here, we show that early expression of Mycb induces expression of genes like ascl1a, a known activator of lin28a in MGPCs. Notably, mycb is simultaneously activated by Ascl1a and repressed by Insm1a in regenerating retina. Here, we unravel a dual role of Mycb in lin28a expression, both as an activator through Ascl1a in MGPCs and a repressor in combination with Hdac1 in neighboring cells. Myc inhibition reduces the number of MGPCs and abolishes normal regeneration. Myc in collaboration with Hdac1 inhibits her4.1, an effector of Delta–Notch signaling. Further, we also show the repressive role of Delta–Notch signaling on lin28a expression in post-injured retina. Our studies reveal mechanistic understanding of Myc pathway during zebrafish retina regeneration, which could pave way for therapeutic intervention during mammalian retina regeneration.
Keywords: Cellular; Reprogramming; Muller glia–derived progenitor cells